Designing UHF RFID tag antennas with Barcode shape for dual‐technology identification. Issue 12 (6th September 2022) - Zannas, Konstantinos; Chietera, Francesco P.; Abdelnour, Abanob; Kaddour, Darine; Colella, Riccardo; Catarinucci, Luca; Duroc, Yvan; Tedjini, Smail
Abstract: In this paper, a novel methodology to design Ultra High Frequency Radio‐Frequency IDentification (UHF RFID) tag antennas with Barcode layout is proposed with the challenging goal of "fusing" both technologies in a single device. Specifically, after a brief recall of the well‐known barcode standard, a procedure to design meandered barcode‐shaped UHF RFID tags is introduced and discussed leveraging on electromagnetic evidence. The main steps of the proposed method are described by highlighting the constraints inherited by both the adopted technologies, as well as the useful opportunities to automatise the entire antenna design process after a preliminary simulation campaign through a full‐wave simulator. Different RFID‐Barcode tag antennas are designed, manufactured, and characterised in terms of maximum reading range and tag sensitivity. Obtained results demonstrate the validity of the proposed approach.